Pengaruh Media Augmented Reality terhadap Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Nurul Rizki Amalia; Icha Peratiwi Sihotang; Nurhayani Nurhayani; Siti Rafiqah Sam (FONDATIA, 2023)
This study looked at the effect of Augmented reality media on students' critical thinking skills. This research was a quantitative study conducted with a population of students in grade 4 with two sample,rooms 4A and 4B,namely the control class and the experimental class,where the control class is given learning that is usually done in class while the experimental class given learning using Augmented reality media. The result, it was found that students' critical thinking skills were influenced by Augmented reality media. Where in the process of learning about the material types of animal food students are directed to see and observe holograms and then to see students' critical thinking skills as evidenced through objective essay tests. The experimental method provides students with direct learning experiences, makes learning more interesting and improves student learning outcomes. These data encourage this research to recommend teachers to use Augmented reality technology in elementary science learning to improve students' critical thinking skills.